Self-consumption through power-to-heat and storage for enhanced PV integration in decentralised energy systems. (15th March 2018) - Schwarz, Hannes; Schermeyer, Hans; Bertsch, Valentin; Fichtner, Wolf
Highlights: Framework considering inter-dependent uncertainty of supply, demand and prices. Stochastic programming reduces the risk of insufficient investment decisions. Thermal storages prove more profitable than electrical storages. The integration of PV is highly dependent on the pricing mechanism. Pricing mechanisms strongly influence the power exchange with the grid. Abstract: Many countries have adopted schemes to promote investments into renewable energy sources resulting, among others, in a high penetration of solar PV energy. The system integration of the increasing amount of variable electricity generation is therefore a highly important task. This paper focuses on a residential quarter with PV systems and explores how heat pumps and thermal and electrical storages can help to integrate the PV generation through self-consumption. However, self-consumption and PV integration are not only affected by technologies but also by pricing mechanisms. This paper therefore analyses the impact of different tariffs on the investment and operation decisions in a residential quarter and its interaction with the external grid. The considered tariffs include a standard fixed per-kilowatt-hour price, a dynamic pricing scheme and a capacity pricing scheme. To account for the interdependent uncertainties of energy supply, demand and electricity prices, we use a module-based framework including a Markov process and a two-stage stochastic mixed-integer program. Analysing a residential quarter in Southern Germany as a case study, we find that the integration of a PV system is economically advantageous for all considered tariffs. The self-consumption rate varies between 58 and 75%. The largest PV system is built when dynamic prices are applied. However, the peak load from the external grid increases by a factor of two under this tariff without any incentive for reduction. In contrast, capacity pricing results in a reduction of the peak load by up to 35%.